Lectotypification of Artemisia rutifolia var. ruoqiangensis (Asteraceae, Anthemideae) - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2020)
The holotype of Artemisia rutifolia var. ruoqiangensis (Asteraceae, Anthemideae), S.K. Wu et al. 2755 (HNWP), was found to be a mixed sheet consisting of two taxa, A. frigida and A. rutifolia var. ruoqiangensis. Lectotypification is proposed for A. rutifolia var. ruoqiangensis herein.